Age-Dependent, Subunit Specific Action of Hydrogen Sulfide on GluN1/2A and GluN1/2B NMDA Receptors - Yakovlev, Aleksey V.; Kurmasheva, Evgeniya D.; Ishchenko, Yevheniia; Giniatullin, Rashid; Sitdikova, Guzel F. (Frontiers in Cellular Neuroscience, 2017)
Hydrogen sulfide (H2S) is an endogenously produced neuroactive gas implicated in many key processes in the peripheral and central nervous system. Whereas the neuroprotective role of H2S has been shown in adult brain, the action of this messenger in newborns remains unclear. One of the known targets of H2S in the nervous system is the N-methyl-D-aspartate (NMDA) glutamate receptor which can be composed of different subunits with distinct functional properties. In the present study, using patch clamp technique, we compared the effects of the H2S donor sodium hydrosulfide (NaHS, 100 µM) on hippocampal NMDA receptor mediated currents in rats of the first and third postnatal weeks. This was supplemented by testing effects of NaHS on recombinant GluN1/2A and GluN1/2B NMDA receptors expressed in HEK293T cells. The main finding is that NaHS action on NMDA currents is age-dependent. Currents were reduced in newborns but increased in older juvenile rats. Consistent with an age-dependent switch in NMDA receptor composition, in HEK239T cells expressing GluN1/2A receptors, NaHS increased NMDA activated currents associated with acceleration of desensitization and decrease of the deactivation rate. In contrast, in GluN1/2B NMDA receptors, which are prevalent in newborns, NaHS decreased currents and reduced receptor deactivation without effect on the desensitization rate. Adenylate cyclase inhibitor MDL-12330A (10 µM) did not prevent the age-dependent effects of NaHS on NMDA-evoked currents in pyramidal neurons of hippocampus. The reducing agent dithiothreitol (2 mM) applied on HEK293T cells prevented facilitation induced by NaHS on GluN1/2A NMDA receptors, however in GluN1/2B NMDA receptors the inhibitory effect of NaHS was still observed. Our data indicate age-dependent effect of H2S on NMDA receptor mediated currents determined by glutamate receptor subunit composition. While the inhibitory action of H2S on GluN1/2B receptors could limit the excessive activation in early age, the enhanced functionality of GluN1/2A receptor in the presence of this gasotransmitter can enlarge synaptic efficacy and promote synaptic plasticity in adults.